A Radical Demand Effect: Early US Feminists and the Married Women's Property Acts. Issue 1 (3rd June 2015) - McCammon, Holly J.; Arch, Sandra C.; Bergner, Erin M.
Abstract : Numerous scholars consider the economic origins of the late-nineteenth- and early-twentieth-century US married women's property acts. Researchers investigate how economic downturns and women's inroads into business spurred lawmakers to reform property laws to give married women the right to own separate property. Such economic explanations, however, are only a partial story. Our investigation reveals the important role of women's collective activism in winning these legal changes. Women mobilized for property rights often as they pressed for voting rights and, in one case, as they campaigned for an equal rights amendment. We examine circumstances leading to passage of married women's property acts in seven states to show that as women mobilized for property rights alongside voting rights or a broader equal rights law, a radical demand effect unfolded. Lawmakers often considered demands for woman suffrage or an equal rights amendment as more far-reaching and thus more radical and threatening. Such feminist demands, then, provided a foil for property-rights activism, and the contrast led lawmakers to view property demands as more moderate. In addition, as they pressed for these combined reforms, women often engaged in hybrid framing that allowed them to moderate their demand for property reforms by linking their property goals to beliefs already widely accepted. The confluence of these circumstances led political leaders to deem property changes as more moderate and acceptable in an effort to steer feminists away from their radical goals. In the end, the radical demand effect created a political opportunity for passage of the married women's property acts.